Mendengar dalam Al-Qur’an: Studi Analisis tentang Keistimewaan As-Sam’u dalam QS. An-Nahl [16]: 78 Perspektif Tafsir al-Jawahir - Muhammad Zulfikar Nur Falah (Fakultas Ushuluddin dan Dakwah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2024)
This article talks about listening in the Al-Qur'an based on Tanthawi Jawhari's analysis of the privileges of as-Sam'u with al-Jawahir's interpretation. The potential of the five senses given by Allah Swt. to humans, even leading to the abyss of error. The sense of hearing plays a role in human life to reflect on this potential in order to create only goodness. This research method uses descriptive analysis obtained through library research, with relevant and reliable sources such as books, journals, theses, theses, dissertations, and so on. Before obtaining an understanding of the implications of this research, the author first describes the biography of Tanthawi Jawhari, and the profile of his book of interpretation. Implicitly, this is so reflective, because it is able to reveal the truth behind the nature of science contained in the meanings of accessories in the Al-Qur'an. The series, the specialty of as-Sam'u in the Al-Qur'an which is focused on the QS. an-Nahl [16]: 78, in the interpretation of al-Jawahir emphasizing his position as qulūbun ya'qilūna, basically it has been included in this research by coordinating systematically by reflecting on being grateful for the blessings of Allah Swt. which must be supported by knowledge.